2012
DOI: 10.1586/era.12.98
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up procedures for non-muscle-invasive bladder cancer: an update

Abstract: Bladder carcinoma is the most common malignancy of the urinary tract. Approximately 75-85% of patients present with a disease that is confined to the mucosa (stage Ta, carcinoma in situ) or submucosa (stage T1). The stratification of patients to low-, intermediate- and high-risk groups represents the cornerstone for the indication of adjuvant and follow-up treatment. Owing to the high recurrence rate of bladder tumors, a surveillance protocol is recommended to all patients. Currently, the combination of cystos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…The most common bladder carcinomas are derived from urothelium and are perceived to arise by at least two separate mechanisms. The nonmuscle invasive bladder tumors (Tis, Ta, and T1) account for most of the urothelial carcinomas that are confined to mucosa or submucosa (14). Remaining urothelial carcinomas are invasive that arise either de novo or from high-grade carcinoma in situ (15,16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common bladder carcinomas are derived from urothelium and are perceived to arise by at least two separate mechanisms. The nonmuscle invasive bladder tumors (Tis, Ta, and T1) account for most of the urothelial carcinomas that are confined to mucosa or submucosa (14). Remaining urothelial carcinomas are invasive that arise either de novo or from high-grade carcinoma in situ (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…In the patients with the TaG1 + TaG2 diseases the presence of the mutations and the noncarrier status for the variant allele was associated with a 2.53 increased risk of the tumor recurrence. The current strategy for follow-up treatment is based on risk stratification, dependent on recurrence and progression scores (14). In clinical trial, bacillus Calmette-Guérin in combination with IFN alpha-2B has been shown to be effective in reducing the recurrence and progression (23).…”
Section: Discussionmentioning
confidence: 99%
“…Among bladder cancers, urothelial carcinoma is by far the most prevalent histologic type, with squamous cell carcinoma and adenocarcinoma making up less than 5% of cases [20]. Per patient, the cost of bladder cancer management is the highest among all tumors, due to the need for long-term monitoring with regular cystoscopy, imaging, and urine cytology [2123]. …”
Section: Discussionmentioning
confidence: 99%
“…NMIBCs are characterized by frequent mutations in the fibroblast growth factor receptor 3 ( FGFR3 ) and three of the five human RAS genes such as Harvey rat sarcoma viral oncogene homolog ( HRAS ), Kirsten rat sarcoma viral oncogene homolog ( KRAS ), and neuroblastoma RAS viral (v-ras) oncogene homolog ( NRAS ) [79]. Also, a large proportion of human bladder tumors show alterations in some of the phosphatidylinositol 3-kinase ( PI3K ) pathway components; in particular, the phosphatidylinositol 3-kinase catalytic subunit alpha ( PIK3CA ) gene [10] that is involved in controlling cell growth, survival, and proliferation and has been considered a promising target for cancer therapy [11, 12].…”
Section: Introductionmentioning
confidence: 99%